2021
DOI: 10.1075/ijlcr.20015.van
|View full text |Cite
|
Sign up to set email alerts
|

Applying phraseological complexity measures to L2 French

Abstract: This study partially replicates Paquot’s (2018, 2019) study of phraseological complexity in L2 English by investigating how phraseological complexity compares across proficiency levels as well as how phraseological complexity measures relate to lexical, syntactic and morphological complexity measures in a corpus of L2 French argumentative essays. Phraseological complexity is operationalized as the diversity (root type-token ratio; RTTR) and sophistication (pointwise mutual information; PMI) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
5
7
0
Order By: Relevance
“…However, phraseological diversity, operationalized as the root type-token ratio (RTTR) of the units, was not significantly different across proficiency levels. Similar results were reported by Vandeweerd, Housen, and Paquot (2021) who conducted a partial replication study using L2 French argumentative essays (B2-C2). While the diversity of adjectival modifiers did increase significantly from C1 to C2, this measure was not found to be an important predictor of the scores given to a text by professional raters, when controlling for other aspects of complexity (i.e., lexical, syntactic, morphological).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, phraseological diversity, operationalized as the root type-token ratio (RTTR) of the units, was not significantly different across proficiency levels. Similar results were reported by Vandeweerd, Housen, and Paquot (2021) who conducted a partial replication study using L2 French argumentative essays (B2-C2). While the diversity of adjectival modifiers did increase significantly from C1 to C2, this measure was not found to be an important predictor of the scores given to a text by professional raters, when controlling for other aspects of complexity (i.e., lexical, syntactic, morphological).…”
Section: Introductionsupporting
confidence: 85%
“…Regarding French, which is the target language of the learners in our study, no one has yet compared the development of phraseology across modes, but phraseological complexity has been shown to be associated with proficiency separately in each modality (Forsberg, 2010;Vandeweerd et al, 2021) 4 and has been shown to increase over time during a study abroad (Edmonds & Gudmestad, 2021). While these studies suggest that phraseology develops with proficiency in French, no study has yet traced the development of phraseological complexity in terms of diversity and sophistication over time, nor compared the longitudinal development across oral and written tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The current study, therefore, aims to determine the extent to which measures of phraseological complexity are predictive of oral versus written French proficiency scores in the context of a high-stakes language assessment exam. In line with previous research, we expect that measures of phraseological complexity will be predictive of proficiency even when controlling for the lexical complexity of a text (Vandeweerd et al, 2021). This would suggest that raters are sensitive to complexity not just at the level of lexis but also at the lexis–grammar interface (i.e., that phraseological measures are not simply a subset of lexical complexity measures) as argued by Paquot, Gries, and Yoder (2021).…”
Section: Introductionsupporting
confidence: 85%
“…With regard to French, the target language of the learners in our study, phraseological complexity has also been found to increase with proficiency both in oral production (Forsberg, 2010), and in written production (Vandeweerd et al, 2021). Only one study thus far has directly compared phraseological complexity across modes, however.…”
Section: Introductionsupporting
confidence: 55%
“…Apart from offering the possibility to compare different results, replication studies can also enable us to compare different operationalizations of the same variable(s) (see e.g. Omidian et al 2021;Vandeweerd et al 2021). Sönning & Werner (2021: 1182 mention the following list of problems that have been identified as potential causes of non-replicability:…”
Section: Introductionmentioning
confidence: 99%